Perencanaan Struktur Baja Gedung Kantor Koperasi Lima Lantai: Analisis Kekuatan dan Ketahanan Gempa Berdasarkan SNI 1726 dan SNI 1729 - Rheznandya Marel; Farrel Al Fasha Saputra; Amin Wakhid; Eko Rudi Utomo; Nor Hidayati (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines the structural planning of a five-story cooperative office building using a steel structural system, with emphasis on strength performance and seismic resistance in accordance with SNI 1726 and SNI 1729. The research adopts a quantitative structural engineering approach through three-dimensional modeling and dynamic analysis using the response spectrum method. Seismic parameters were determined based on site location, soil classification, and building risk category, and then used to develop the design response spectrum. Structural performance was evaluated by comparing internal forces on beams and columns with the nominal capacities of steel members under combined gravity and seismic loading. The analysis confirms that all structural elements satisfy strength requirements and comply with the strong column–weak beam concept, ensuring adequate ductility. Global structural behavior was assessed through inter-story drift, base shear distribution, and deformation patterns, all of which remain within allowable limits. The results indicate that the planned steel structural system provides sufficient stiffness, stability, and seismic resistance for medium-rise office buildings in seismic regions.